An In-depth Investigation of the Primordial Cluster Pair ASCC 19 and ASCC 21 - Qingshun Hu; Yuting Li; Mingfeng Qin; Chenglong Lv; Yang Pan; Yangping Luo; Shuo Ma (The Astronomical Journal)
Utilizing Gaia data from the literature, we report a new young (∼8.9 Myr) cluster pair, ASCC 19 and ASCC 21, located near the Orion star-forming complex. The clusters are separated by a 3D distance of 27.00 ± 7.51 pc. Both clusters share a common age (Log(age) = 6.95 ± 0.05), similar radial velocities (RV = 21.34 ± 4.47 km s ^−1 for ASCC 19 and RV = 20.05 ± 3.86 km s ^−1 for ASCC 21), and comparable metallicities ([Fe/H] = −0.14 ± 0.25 dex for ASCC 19 and [Fe/H] = −0.12 ± 0.04 dex for ASCC 21, from LAMOST-DR11). These similarities suggest that the clusters likely originated from the fragmentation of the same molecular cloud, forming a primordial cluster pair. Furthermore, the formation of the two clusters is attributed to the coalescence of multiple subclusters, as inferred from the distribution analysis between metal abundances and distances to clusters’ centers. Neither cluster shows significant mass segregation. Their members with RVs exceeding 100 km s ^−1 are young variables. Additionally, a tidal interaction between the clusters is observed. Comparisons of the Roche radius with tidal radii, as well as velocity difference with orbital velocity, suggest that the pair is an unbound system, that is, a double cluster. Finally, orbital motion simulations show that the clusters will not merge into a single system.